Clinical researchTRAIL protein expression in breast cancer cells correlates with nuclear grade - Bilski, Adam; Pasz-Walczak, Grażyna; Kubiak, Robert; Sek, Piotr; Chalubinska, Justyna; Fendler, Wojciech; Wronski, Konrad; Piekarska, Anna; Pluta, Piotr; Potemski, Piotr; Jeziorski, Arkadiusz; Piekarski, Janusz (Archives of Medical Science, 2010)
Introduction : TRAIL protein may serve as an escape mechanism for cancer cells from the immune response. The aim of the study was to assess whether the presence of TRAIL protein correlates with unfavourable prognostic factors in breast carcinoma. Material and methods: The study group was composed of breast cancer patients treated surgically in the Department of Surgical Oncology, Medical University of Lodz, Poland, from January to December 2003. Inclusion criteria for the study were fulfilled by 117 women. The immunohistochemical study of TRAIL protein expression was performed in 118 breast carcinomas diagnosed in the study group. TRAIL protein expression was correlated with other variables: tumour size, lymph node status, grade, histological type of carcinoma, oestrogen and progesterone receptor status, HER2 expression, presence of lymphovascular invasion and age of the patient. Results : Expression of TRAIL protein was present in 73% of breast carcinomas. The percentage of TRAIL-expressing breast carcinoma cells correlated with the nuclear grade ( = 0.26, p < 0.05; Tau Kendall test). The intensity of TRAIL expression (intensity of staining) in breast carcinoma cells correlated with the nuclear grade ( = 0.15, p < 0.05; Tau Kendall test). TRAIL expression in breast carcinoma did not correlate with other studied variables. Conclusions: Our analysis revealed that expression of TRAIL protein in breast carcinoma cells correlates with nuclear grade of carcinoma.